Effect of Different Cytokinins and Auxins on Microopropagation and Callogenesis in Amaryllus (Amaryllis vittata) - Ali, Aamir; Shaheen Niazi, Rabia; Yasmin, Saira; Majid, Abdul; Huma Naveed, Naima (Asian Journal of Chemistry, 2012)
In vitro propagation of Amaryllis vittata was carried out to explore the regenerative and callogenic potential of different explants (both meristem and twin scales were used as explants) and to study the influence of different concentrations and combinations of various phytoharmones along with varying environmental conditions like temperature and light on in vitro shoot initiation, formation, multiplication and rooting. Shoot formation response (92 %) from meristem was obtained on Murashige and Skoog’s medium (MS) containing 2.5 mg/L of kinetin after 11 days of inoculation. When twin scales were used as explants 92 % shoot initiation response was obtained on MS medium supplemented with 2 mg/L 6-benzylamino purine (BAP) + 0.25 mg/L a-naphthalene acetic acid (NAA). For multiplication of in vitro developed shoots, the best response was obtained on MS medium containing 2 mg/L BAP + 0.25 mg/L NAA with 4.4 shoots per culture vial having an average shoot length of 4.18 after 10 days of inoculation. For rooting, best response was obtained on ½MS medium supplemented with 1.0 mg/L NAA + 0.5 mg/L indole butyric acid (IBA) where 4.4 shoots were obtained having an average shoot length of 3.7 cm in about 10 days of explants inoculation. A temperature of 26 ºC and photoperiod of 16 h and 8 h dark in every 24 h cycle proved best for in vitro culturing of amaryllis.